2023
DOI: 10.3390/electronics12204299
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Advanced Techniques and Vital Tools for Detecting Malware Intrusion

Vatsal Vasani,
Amit Kumar Bairwa,
Sandeep Joshi
et al.

Abstract: In this paper, we explore how incident handling procedures are currently being implemented to efficiently mitigate malicious software. Additionally, it aims to provide a contextual understanding of diverse malcodes and their operational processes. This study also compares various ways of detecting adware against a selection of anti-virus software. Moreover, this paper meticulously examines the evolution of hacking, covering the methods employed and the actors involved. A comparative analysis of three prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Studies revealed that dynamic analysis methods, leveraging behavioral patterns and system interactions, offered promising results in identifying ransomware with high accuracy [10], [15], [16], [17]. Research on static analysis, focusing on examining the code without execution, also contributed to early detection capabilities but faced limitations due to obfuscation techniques used by malware authors [18], [19], [20], [21]. Hybrid approaches, combining both static and dynamic analysis, were identified as comprehensive solutions, enhancing detection rates and reducing false positives [17], [22], [23].…”
Section: A Detection Techniques and Toolsmentioning
confidence: 99%
“…Studies revealed that dynamic analysis methods, leveraging behavioral patterns and system interactions, offered promising results in identifying ransomware with high accuracy [10], [15], [16], [17]. Research on static analysis, focusing on examining the code without execution, also contributed to early detection capabilities but faced limitations due to obfuscation techniques used by malware authors [18], [19], [20], [21]. Hybrid approaches, combining both static and dynamic analysis, were identified as comprehensive solutions, enhancing detection rates and reducing false positives [17], [22], [23].…”
Section: A Detection Techniques and Toolsmentioning
confidence: 99%
“…Historical analyses of ransomware mitigation strategies highlighted the initial reliance on signature-based detection methods, which were quickly found to be ineffective against polymorphic and zero-day attacks [26,27,28,29]. The development of behavior-based detection tools represented a significant advancement, offering the ability to identify ransomware based on its actions rather than its signature [1,30,31].…”
Section: Existing Ransomware Detection and Prevention Toolsmentioning
confidence: 99%
“…In the field of malware detection using deep learning, there are several challenges that need to be addressed and promising avenues for future research [23, [73][74][75][76][77][78][79][80][81][82][83][84][85]. Figure 5 illustrates the open challenges associated with the deep learning-powered malware detection in cyberspace.…”
Section: Open Challengesmentioning
confidence: 99%